Analisis Pengelolaan Retribusi Parkir Sebagai Strategi Peningkatan Pendapatan Asli Daerah - Usivianti Latifah Humairah; Endah Dwi Kusumastuti; Iyeh Supriatna (Indonesian Accounting Research Journal, 2021)
Abstract: This study was conducted to determine the performance of the Bandung City Government in managing parking fees as a source of increasing PAD and providing useful solutions and recommendations to obtain effective strategies to increase Regional Original Income. The method used in this research is descriptive qualitative. Data collection techniques used are interviews with related parties, field observations and viewing existing documentation. The research results obtained are parking retribution management activities that have been carried out in the city of Bandung in the implementation and control aspects, some are found to be still not in accordance with the Standard Operating Procedures, rules and regulations set. These discrepancies include the use of parking rates that are not in accordance with Perda Number 04 of 2017 which has used progressive rates, there are still many parking locations on public roads controlled by illegal/illegal parking attendants, the use of Electronic Parking Terminals (TPE) is still not optimal and limited. field supervisors on the use of Electronic Parking Terminals (TPE).